A water rights trading approach to increasing inflows to the Aral Sea - Bekchanov, Maksud; Ringler, Claudia; Bhaduri, Anik (Wiley, 2018)
Tremendous development of irrigation since the 1960s combined with unbalanced water resources management led to the destruction of the ecosystems in the delta zone and the gradual desiccation of the Aral Sea, once the fourth largest freshwater lake of the world. Command-and-control based water management in the Aral Sea Basin (ASB) inherited from Soviet times did not create any incentives for investing in improved irrigation infrastructure, adopt water-wise approaches, and thus maintain flows into the Aral Sea. This study examined the potential for market-based water allocation to increase inflows to the Aral Sea while maintaining stable agricultural incomes. We find that a water trading system can improve inflows to the Aral Sea but would require significant compensation for agricultural producers. Agricultural producers can use the compensation payments to cope with reduced water supply by improving irrigation and conveyance efficiencies and by developing alternative rural activities such as livestock grazing, agro-processing, and cultivation of low water consumptive crops. We also find that a water trading system would be more efficient if it includes both trade among irrigation sites and between sites and instream uses.